Adsorption Kinetics Of Phenolic Compunds Onto Activated Carbon. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (2004)
Aqueous-phase adsorption equilibrium and kinetic mechanism of phenol, 3-chlorophenol and o-cresol onto Norit Granular Activaied Carbon (NAC 1240) were studied in a batch system at temperature of 30oC,agitation speed of 120 rpm, initial phenol concentrations of 25-200 mg/l.